GAMBARAN KEPERCAYAAN KONSUMEN DALAM BERBELANJA ONLINE DI FJB KASKUS - Putu Beny Sutrisna; Dewi Puri Astiti (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2015)
As one of the sites used for marketing products, FJB Kaskus cannot be separated from the scams that a common in e-commerce business. Nevertheless, the velocity of money in FJB Kaskus has reached 100 billion dollars each month in which the figure has even beat omzet of Amazon.com for sale to the Regional Indonesian (Hartanto, 2009). This shows the importance of trust as a major factor that must be built in order to be able to attract consumers to buying. Trust not just be recognized by the other party or e-tailers due to the trust must be created from scratch and can be proven (Rofiq, 2007). Trust cannot be easily recognized by other party or e-tailers because trust must be created from beginning and can be proven (Rofiq, 2007). This research was aimed to determine the overview of consumer trust in online shopping at FJB Kaskus. This research used qualitative methods and phenomenology design. Data were collected by using interview and observation technique with 5 respondents with experience in online shopping repeatedly at FJB Kaskus. The result of this research shows that consumer trust can be described using trusting belief and trusting intention. Besides that, website information and seller information may affect consumer trust in online shopping at FJB Kaskus. Key words: consumer trust, online shopping, FJB Kaskus.